Self-assembly of human papillomavirus type 1 capsids by expression of the L1 protein alone or by coexpression of the L1 and L2 capsid proteins. - Hagensee, M E (1993)
Vaccinia virus vectors were used to express the major (L1) and minor (L2) capsid proteins of human papillomavirus type 1 (HPV-1) with the vaccinia virus early (p7.5K) or late (pSynth, p11K) promoters. All constructs expressed the appropriate-sized HPV proteins, and both L1 and L2, singly or in combination, localized to the nucleus. Capsids were purified by cesium chloride density gradient centrifugation from nuclei of cells infected with a vaccinia virus-L1 (vac-L1) recombinant or a vac-L1-L2 recombinant but not from vac-L2-infected cells. Electron microscopy showed that the particles were 55 nm in diameter and had icosahedral symmetry. Immunogold-labeled antibodies confirmed the presence of the L1 and L2 proteins in the HPV-1 capsids. Capsids containing L1 alone were fewer and more variable in size and shape than capsids containing the L1 and L2 proteins. The L1-plus-L2 capsids were indistinguishable in appearance from HPV-1 virions obtained from plantar warts. The ability to produce HPV capsids in vitro will be useful in many studies of HPV pathogenicity.